Temporal myofascial segmentation for multilayer reconstruction of middle cranial fossa floor after extradural subtemporal approach to the clival and paraclival region. Issue 10 (7th August 2019) - Gagliardi, Filippo; Piloni, Martina; Bailo, Michele; Gragnaniello, Cristian; Nocera, Gianluca; Boari, Nicola; Spina, Alfio; Caputy, Anthony J.; Mortini, Pietro
Abstract: Background: Skull‐base reconstruction represents a concern after resection of middle fossa (MF) tumors by the extradural subtemporal transzygomatic approach (ESTZ). Regional pedicled flaps appear to be the best option. This study describes a technique for temporal myofascial segmentation to harvest a multilayered vascularized flap for MF reconstruction, which might preserve temporal muscle (TM) function and its blood supply. Methods: The technique to harvest a combined segmented temporal myofascial flap (CSTMF) is described. The flap consists in a temporal fascial (TFF) and a muscle flap (TMF), composed by TM anterior‐medial bundle (AMB). Results: CSTMF provides wide coverage of dural lining, through the TFF, and of dead‐space, through the TMF. The possibility to tailor TMF according to the need, anatomically preserving the blood supply, enables to significantly increase its volume. Conclusion: CSTMF represents an effective option as regional multilayered pedicled flap for MF reconstruction, potentially preserving TM function and minimizing the cosmetic impact.